The severity of anxiety-depressive states and somatization in adolescents and youth with different online behaviors in Tuva - Fotekova, Tatiana A.; Vlasova, Evgenia N.; Mitrukhina, Svetlana V.; Mongush, Chochagai N. (The New Research of Tuva, 2024)
The article analyzes the issues of the psycho-emotional state of adolescents and young people in the Republic of Tuva, who differ in the types of internet use: adaptive, maladaptive, and pathological. The study was based on the results of an online survey conducted by random sampling in 2023, including 1028 participants: 76 Russians and 952 Tuvans. To assess the psychological well-being of the individuals involved in the study, the SCL-90-R questionnaire was used, which identifies nine different symptoms. Three of these symptoms were analyzed: anxiety, depression, and somatization, which reflect the distress caused by feelings of physical discomfort. A comparative analysis of indicators among groups differing in online behavior and ethnicity is presented. The Russian part of the sample, regardless of the online behavior variant, was characterized by higher levels of somatization (28.9% of Russians and 24.4% of Tuvans), depression (20% and 11.9%), and anxiety (25.4% and 12.1%). Differences were also revealed among representatives of the compared ethnic groups with similar online behavior. Among both Russians and Tuvans with a pathological use of the Internet, higher levels of somatization, anxiety, and depression were more common. Ethnic differences manifested in a higher number of people with high somatization and depression levels in the Russian group with adaptive online behavior compared to the Tuvan group with similar behavior. Anxiety levels were more frequently observed among Russian adolescents and young adults with a pathological online behavior pattern (71.4% and 28.6%).